Fibrin(ogen) Is Constitutively Expressed by Differentiated Intestinal Epithelial Cells and Mediates Wound Healing - Seltana, Amira; Cloutier, Gabriel; Reyes Nicolas, Vilcy; Khalfaoui, Taoufik; Teller, Inga C.; Perreault, Nathalie; Beaulieu, Jean-François (Frontiers in Immunology, 2022)
The functional integrity of the intestine is ensured by the constant renewal of its simple epithelium. Superficial denuding of the epithelial cell layer occurs regularly and is rapidly corrected by a process called restitution which can be influenced by various soluble and insoluble factors. Epithelial cell interaction with the extracellular matrix greatly influences the healing process by acting on cell morphology, adhesion and migration. The functional contribution of a fibrin(ogen) matrix in the intestine was studied under physiological and pathological contexts. Our results (immunofluorescence, immuno-electron microscopy and qPCR) show that fibrin(ogen) is a novel component of the basement membrane associated with the differentiated epithelial cell population in both the small intestine and colon. Fibrin(ogen) alone is a weak ligand for epithelial cells and behaves as an anti-adhesive molecule in the presence of type I collagen. Furthermore, the presence of fibrin(ogen) significantly shortens the time required to achieve closure of wounded epithelial cell monolayers and co-cultures in a PI3K dependent manner. In human specimens with Crohn's disease, we observed a major accumulation of fibrin(ogen) throughout the tissue as well as at denuded sites. In mice in which fibrin formation was inhibited with dabigatran treatment, dextran sodium sulfate administration provoked a significant increase in the disease activity index and pathological features such as mucosal ulceration and crypt abscess formation. Taken together, these results suggest that fibrin(ogen) contributes to epithelial healing under both normal and pathological conditions.